Prevalence of thyroid dysfunction and its association with controlled and uncontrolled type 2 diabetes mellitus in northern Andhra Pradesh population: a retrospective study - D. K. V., Prasad; T. S., Prabhakara Rao; G., Krishna Murthy (International Journal of Research in Medical Sciences, 2017)
Background: The two important endocrinopathies, diabetes mellitus and thyroid dysfunction are interrelated to each other where the correlation is poorly understood. The thyroid dysfunction is more frequent in diabetics than general population. The present study was aimed to know the prevalence of thyroid dysfunction in type 2 diabetes mellitus (T2DM) and its association with controlled and uncontrolled T2DM. Methods: A retrospective study of 600 T2DM patients between 13-60 years of age with known thyroid status were included and the following parameters were examined: age, sex, body mass index (BMI), fasting blood sugar (FBS), HbA1C, free triiodothyronine (fT3), free tetraiodothyronine (fT4) and thyroid stimulating hormone (TSH). Results: The prevalence of thyroid dysfunction in T2DM patients was found to be 26.5% whereas 9% in healthy controls. Significantly elevated levels of FBS, HbA1C and TSH were observed whereas the levels of fT3, fT4 were found to be low in patients when compared to controls. Subclinical hypothyroidism (SCH) in diabetics (both controlled and uncontrolled) was more prevalent (15%) than it was found in healthy controls (5%). Similarly, overt hypothyroidism was also found to be high in diabetic patients (6%) as compared to healthy controls (2%). Significant difference (p <0.05) in the levels of TSH was found between group I (Controlled T2DM) and II (uncontrolled T2DM patients), also between groups II and III (Controls). Group II patients were found to have significant low levels of fT3 as compared to other two groups (Group I and III) (p<0.005). Conclusions: As SCH is more frequent in T2DM diabetes mellitus and untreated SCH patients have higher rate of complications, periodical screening is advised for thyroid dysfunction to prevent micro vascular and cardiovascular complications.